The Role of Hydrogen-Peroxide (H2O2) Produced by Vaginal Microbiota in Female Reproductive Health - Eva Miko; Aliz Barakonyi (Antioxidants, 2023)
Female reproductive health is strongly associated with healthy vaginal microbiota, which is thought to be ensured by the dominance of certain Lactobacillus species. Lactobacilli control the vaginal microenvironment through several factors and mechanisms. One of them is their ability to produce hydrogen peroxide (H2O2). The role of Lactobacillus-derived H2O2 in the vaginal microbial community has been intensively investigated in several studies with many designs. However, results and data are controversial and challenging to interpret in vivo. Defining the underlying mechanisms responsible for a physiological vaginal ecosystem is crucial since it could directly affect probiotic treatment attempts. This review aims to summarize current knowledge on the topic, focusing on probiotic treatment possibilities.